Analysis of Protein Composition Using Multidimensional Chromatography and Mass Spectrometry. (3rd November 2014) - Link, Andrew J.; Washburn, Michael P.
Abstract: Multidimensional liquid chromatography of peptides produced by protease digestion of complex protein mixtures followed by tandem mass spectrometry can be coupled with automated database searching to identify large numbers of proteins in complex samples. These methods avoid the limitations of gel electrophoresis and in‐gel digestions by directly identifying protein mixtures in solution. One method used extensively is named Multidimensional Protein Identification Technology (MudPIT), where reversed‐phase chromatography and strong cation–exchange chromatography are coupled directly in a microcapillary column. This column is then placed in line between an HPLC and a mass spectrometer for complex mixture analysis. MudPIT remains a powerful approach for analyzing complex mixtures like whole proteomes and protein complexes. MudPIT is used for quantitative proteomic analysis of complex mixtures to generate novel biological insights. © 2014 by John Wiley & Sons, Inc.